2018
DOI: 10.3389/fmicb.2018.01932
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Dehydrogenase I Contributes to Growth and Sporulation Under Low Oxygen Condition via Detoxification of Acetaldehyde in Metarhizium acridum

Abstract: The entomopathogenic fungi encounter hypoxic conditions in both nature and artificial culture. Alcohol dehydrogenases (ADHs) are a group of oxidoreductases that occur in many organisms. Here we demonstrate that an alcohol dehydrogenase I, MaADH1, in the locust-specific fungal pathogen, Metarhizium acridum, functions in acetaldehyde detoxification mechanism under hypoxic conditions in growth and sporulation. The MaADH1 was highly expressed in sporulation stage under hypoxic conditions. Compared with a wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…Acetaldehyde and different types of alcohols were generally high in relative concentration across all Mortierella s. l. strains ( Table 3 ). These compounds’ reported functions vary among fungal species, but they certainly play a role in stress response and/or defense mechanisms [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acetaldehyde and different types of alcohols were generally high in relative concentration across all Mortierella s. l. strains ( Table 3 ). These compounds’ reported functions vary among fungal species, but they certainly play a role in stress response and/or defense mechanisms [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…DEGs with higher expression levels in mycelial growth than inhibited samples were listed in Table 3 . Some genes involved in mycelial growth, such as Alcohol dehydrogenase , catalase A and chitinase were lower expressed in CZA than other samples [ 26 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…DEGs with higher expression levels in mycelial growth than inhibited samples were listed in Table 3. Some genes involved in mycelial growth, such as Alcohol dehydrogenase, catalase A and chitinase were lower expressed in CZA than other samples [26][27][28]. In addition, 20 genes involved in conidial germination or mycelial growth were shown to be up-regulated in WT/CZA, CZA + AA/CZA, and CZA + yeast/CZA from RNA-Seq data.…”
Section: Mrilvc Affects Expression Of Genes Involved In Mycelial Growth and Conidial Germinationmentioning
confidence: 94%
“…In A. nidulans , the alcC gene encoding AdhIIIp is regulated at both the transcriptional and translational levels, induced by anaerobic stress, and required for long-term survival under these anaerobic conditions [ 39 ]. In the entomopathogenic fungus Metarhizium acridum, the Adh1 gene is similarly regulated by oxygen; under hypoxic conditions, the Adh1 gene is up-regulated [ 40 ].…”
Section: Regulation Of the Fungal Adhsmentioning
confidence: 99%
“…The authors suggested that Adh1p activity is required to penetrate and colonize P. xylostella larvae. However, Zhang et al [ 40 ] reported that in M. acridum, the Adh1 gene is not involved in the virulence of Locusta migratoria . In C. albicans, [ 86 ] reported reduced ADH1 gene expression and a lower presence of Adh1p in Candida biofilm cells than in planktonic cells.…”
Section: Regulation Of the Fungal Adhsmentioning
confidence: 99%